Children and Adolescents Mental Health: A Systematic Review of Interaction-Based Interventions in Schools and Communities - García-Carrión, Rocío; Villarejo-Carballido, Beatriz; Villardón-Gallego, Lourdes (Frontiers in Psychology, 2019)
Background: There is growing evidence and awareness regarding the magnitude of mental health issues across the globe, starting half of those before the age of 14 and have lifelong effects on individuals and society. Despite the multidimensional nature of this global challenge, which necessarily require comprehensive approaches, many interventions persist in seeking solutions that only tackle the individual level. The aim of this paper is to provide a systematic review of evidence for positive effects in children and adolescents’ mental health resulting from interventions conducted in schools and communities in which interaction among different agents is an integral component. Methods: An extensive search in electronic databases (Web of Knowledge, SCOPUS, ERIC, and PsycINFO) was conducted to identify interventions in which interactions between peers, teachers, families or other community members or professionals played a role. Their effects on children and adolescents’ mental health were also reviewed. We carried out a systematic review of papers published from 2007 to 2017. Eleven studies out of 384 met the inclusion criteria. Seven of the articles reviewed focus on interventions conducted in schools and promote supportive interactions involving students, teachers, families and mental health professionals. Four of the articles develop interventions that engage community members in dialogic interactions with children and adolescents. Results: Interventions in schools and communities implement strategies that foster supportive interactions among diverse actors including teachers, parents, community members and other professionals. The effects of the mental health interventions reported on children and adolescents’ problems include a decrease in disruptive behaviors and affective symptoms such as depression and anxiety, together with an increase in social skills, as well as an improvement in personal well-being. Conclusions: There is evidence of a positive effect on the mental health of children and adolescents, both in decreasing symptoms of mental disorder and in promoting emotional well-being. Whereas interactions among different actors seem to be a relevant aspect across the interventions, more research is needed to conclude its effect on the outcomes of the studies reviewed.